The pH and Hedonic of Chicken Steak Cooked with Seasoning Contains Cashew Apple Extract - Wisnu Broto; V Priyo Bintoro; Ghassani Ardan Setiawan; Sri Risdhiyanti Nuswantari; Siti Susanti (Journal of Applied Food Technology, 2021)
Cashew apple utilization is less than the cashew itself, due to the cheaper price and therefore often ends up as waste. Extract cashew apple can be applied in chicken steak for marinating as an innovation in food seasoning sauce. This study aims to determine the panelist’s preference for chicken steak marinating with commercial seasoning sauce and marinating with a seasoning sauce that contains cashew apple extract (CAE) on different concentrations of seasoning solution. There were 5 levels of treatment, control treatment (T0) using 40% (v/v) concentration of commercial seasoning, T1, T2, T3, and T4 consecutively using seasoning concentrations 20%, 40%, 60%, and 80% (v/v). The pH of the samples was evaluated with a pH meter, meanwhile, the hedonic test was used to evaluate the preference of the samples. The result showed that the levels of seasoning concentration affected the pH and panelist preference with hedonic assessment over 5 parameters (tenderness, juiciness, taste, aroma, and overall). The increasing seasoning concentration gives more acidic properties indicated by 4,58 pH of. The hedonic assessment showed 60% concentration of seasoning is preferred.